Pemantauan Kualitas Udara Ambien pada Pekerjaan Preservasi Jalan - Raudhati, Emelda (Jurnal Civronlit Unbari, 2024)
Heavy traffic, especially from large vehicles passing through the road, can potentially cause congestion and increase air pollution. Ambient air quality can significantly decrease due to vehicle emissions, impacting public health and environmental quality. This study focuses on monitoring ambient air quality during road preservation work conducted along the route of Jalan Bts. Prov. Sumsel – Tempino – Pal. Sepuluh – Lingkar Timur – Sp. Sijenjang – Pel. Talang Duku in Muaro Jambi Regency.objective of this research is to analyze the ambient air quality at th road preservation work sites. The research method applied is a survey method with the selection of three locations along the road segment: 1. AMP Tempino, located at coordinates LS 01°47’01.23’’ BT 103°28’27.56’’; 2. STA 11+050 located at coordinates LS 01°45’51’’ BT 103°33’23’’; and 3. Ruas Simpang Paal. X, located at coordinates LS 01°40’12’’ BT 103°36’1’’. This research is descriptive in nature, focusing on the observation and analysis of ambient air quality according to the SNI 7119-3:2017 standard for each test parameter. The results show that at the AMP Tempino site, Particulate dust is 46,50 µg/Nm³,Sulfur Dioxide is 99,88 µg/Nm³, and Carbon Monoxide is 6563,05 µg/Nm³. The highest Nitrgen Dioxide level of 47,88 µg/Nm³ was recorded at STA 11+050, and the highest level of Photochemical Oxidants as Ozone at 41,76 µg/Nm³ was found at Ruas Simpang Paal. X. All test parameters are below the standard quality limits. Overall, Carbon Monoxide has the highest concentration across all locations, while Nitrogen Dioxide often shows the lowest values